EKSPLORASI Begonia spp (BEGONIACEAE) DI GUNUNG SIDOLE, KECAMATAN AMPIBABO, KABUPATEN PARIGI MOUTONG, SULAWESI TENGAH INDONESIA - Eka Putri Dayanti; Ramadanil (Biocelebes, 2020)
The study entitled Exploration of Begonia (Begoniaceae) in the Sidole Mountain, Ampibabo district, Parigi Moutong regency the province of Central Sulawesi has been conducted from December 2018 to April 2019. The objective of the research were to record and describe Begonia species from research site. The research by using botanical exploration methods. The results indicated that there were 4 (four) species of Begonia, namely B. aptera Blume, B.rieckei Warb., Begonia sp. 1 and Begonia sp. 2.